2021
DOI: 10.1111/jocn.15630
|View full text |Cite
|
Sign up to set email alerts
|

Communicating prognostic information and hope to families of dying patients in intensive care units: A descriptive qualitative study

Abstract: Aims and objectives To understand how prognostic information is communicated by Jordanian doctors and nurses to the families of dying patients in intensive care units, with an emphasis on exploring how hope and truth telling about patients' poor prognosis are managed. Background Improving end‐of‐life care requires a focus on adequate family–professionals prognostic communication, while maintaining a realistic level of hope and family support. Design A descriptive qualitative approach was applied. Methods Semi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…In this study, TMPs addressed anxiety through continuous respectful communication and multiple individualized counseling sessions. This was consistent with studies conducted in Uganda, South Africa, and Malaysia, which demonstrated TMPs provided personalized counseling, including for families, unlike orthodox doctors [ 8 , 49 , 50 ]. In addition, TMPs understood their patients’ beliefs, values, behavior, and language, meaning they counseled their patients from a cultural perspective that aided the uptake of their counseling messages [ 50 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, TMPs addressed anxiety through continuous respectful communication and multiple individualized counseling sessions. This was consistent with studies conducted in Uganda, South Africa, and Malaysia, which demonstrated TMPs provided personalized counseling, including for families, unlike orthodox doctors [ 8 , 49 , 50 ]. In addition, TMPs understood their patients’ beliefs, values, behavior, and language, meaning they counseled their patients from a cultural perspective that aided the uptake of their counseling messages [ 50 ].…”
Section: Discussionsupporting
confidence: 88%
“…Qualitative studies on physicians’ perceptions of communicating about end-of-life are practically non-existing. However, a recent study has shown that especially outside the Western Hemisphere, health care personnel may have difficulties providing a bad prognosis and hence avoid disclosing it [ 18 ]. It is also noteworthy that the majority of studies on POLST come from the USA.…”
Section: Discussionmentioning
confidence: 99%
“…The nurses in ICU focus on patients and their families to prevent deterioration and improve the patient's condition (Sole et al, 2009), and to deal with life-saving interventions during acute physiological crises, with a particular focus on medical needs and access to technology (Marik, 2010). Good communication is vital to the assessment of symptoms and in promoting patients' participation in decision-making about treatment plans and end-of-life (EOL) decisions (Happ et al, 2004) and giving care to families at this stage (Almansour & Abdel Razeq, 2021;Rivera-Romero et al, 2019). There are various factors that affect communicating care and caring in ICU (Ganz, 2019;Happ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%